2010
DOI: 10.1007/s13213-010-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles of PUFA producing Antarctic bacteria: correlation with RAPD analysis

Abstract: The significance of polyunsaturated fatty acids (PUFA) to humans lies in their biological activity, as precursors for groups of nutritionally important compounds and as essential cellular components. They are also crucial in animals for the proper development of retinal and nervous tissue. In this work, Antarctic sea samples were used to isolate bacterial cultures producing PUFA. Three bacterial strains were isolated from three different samples and they were named as BRI 1, BRI 7 and BRI 28. Percentage of eic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…With the ten random primers, strain J5-3 T shared plenty of polymorphic bands but few monomorphic bands with the type strains in genera Devosia and Pelagibacterium. The monomorphisms, the number of monomorphic bands against the total bands, between strain J5-3 T riboflavina DSM 7230 T ), and 26.3 % (P. halotolerans CGMCC 1.7692 T ), which were low enough to distinguish strain J5-3 T from all the four reference strains [11,22]. The results were consistent with the relatively low 16S rRNA and gyrB gene sequence similarities, which indicated that strain J5-3 T was separated from reference strains.…”
Section: Phylogenetic Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…With the ten random primers, strain J5-3 T shared plenty of polymorphic bands but few monomorphic bands with the type strains in genera Devosia and Pelagibacterium. The monomorphisms, the number of monomorphic bands against the total bands, between strain J5-3 T riboflavina DSM 7230 T ), and 26.3 % (P. halotolerans CGMCC 1.7692 T ), which were low enough to distinguish strain J5-3 T from all the four reference strains [11,22]. The results were consistent with the relatively low 16S rRNA and gyrB gene sequence similarities, which indicated that strain J5-3 T was separated from reference strains.…”
Section: Phylogenetic Analysismentioning
confidence: 91%
“…As a simple, rapid, and efficient molecular marker, RAPD is usually used for germplasm identification and genetic diversity researches [11,19,22,34,38]. After the genomic DNA were extracted from strain J5-3 T and all the four reference strains [18], RAPD analysis was carried out in 50 lL reaction mixture containing 5 lL 109 PCR buffer (Takara), 4 lL dNTP mixture (Takara), 1 U Taq polymerase (Takara), 20 lM primer (Supplementary Table 4), and 20 ng template DNA.…”
Section: Random-amplified Polymorphic Dna (Rapd) Analysismentioning
confidence: 99%
“…We have earlier reported halotolerant organisms from wall scrapings of historical building in India (13) and also from some food samples (14) with an ability to produce industrially useful enzymes. Recently we have characterized some marine isolates from the Antarctic Ocean as well as from the Indian Ocean with respect to their fatty acid profiles (15,32). Comparatively few reports are available on the saline-tolerant proteases from microbial sources.…”
mentioning
confidence: 99%
“…Early studies indicated the n −3 PUFA accumulation was a characteristic of deep-sea bacteria (DeLong and Yayanos, 1986;Wirsen et al, 1987), suggesting that it was a barophilic as much as a lowtemperature adaptation. The capacity for n −3 PUFA production has, however, later been found to be equally widespread in nonbarophilic, cold-adapted bacteria (Henderson et al, 1993;Yano et al, 1997;Cho and Mo, 1999;Nichols, 2003;Frolova et al, 2011), including Arctic and Antarctic strains (Nichols et al, 1993;Jøstensen and Landfald, 1997;Bowman et al, 1998;Jadhav et al, 2010). Mutant studies have unequivocally associated PUFA production in bacteria with cold adaptation, as growth is impaired at low, but not elevated temperatures by knocking out this trait in e.g.…”
Section: Lipid Adaptationmentioning
confidence: 99%